2016
DOI: 10.1002/pi.5172
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular design of specialty polylactides by means of controlled copolymerization and stereocomplexation

Abstract: Among the bio-based polymers thus developed, poly-L-lactide (PLLA) has been the most widely used in many fields because of its excellent cost-property balance.However, the properties and functionalities of PLLA cannot easily be controlled as the conventional petroleum-based polymers, retarding the progress of its manufacturing in large scale. One approach to obtain high-performance and specialty polylactides is to use stereocomplex-type polylactides (sc-PLA) that can be obtained by mixing PLLA and its enantiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 151 publications
(168 reference statements)
0
9
0
Order By: Relevance
“…Stereocontrol in metal-mediated ROP of LA can arise through two mechanisms: (1) enantiomorphic site control and (2) chain-end control. These two mechanisms are not necessarily independent and may both play an important role at different points in the polymerization process . Controlling the physical properties of PLA through metal catalysis, for example, through the stereoselective polymerization of rac -LA ,,, or the copolymerization of LA and other cyclic esters ,,− has become an important avenue toward the widespread replacement of traditional nondegradable plastics with biodegradable options ( vide infra ).…”
Section: Introductionmentioning
confidence: 99%
“…Stereocontrol in metal-mediated ROP of LA can arise through two mechanisms: (1) enantiomorphic site control and (2) chain-end control. These two mechanisms are not necessarily independent and may both play an important role at different points in the polymerization process . Controlling the physical properties of PLA through metal catalysis, for example, through the stereoselective polymerization of rac -LA ,,, or the copolymerization of LA and other cyclic esters ,,− has become an important avenue toward the widespread replacement of traditional nondegradable plastics with biodegradable options ( vide infra ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ability for supramolecular chain extension achieved by capping UPy chains, we took additional advantage of dually associated stereocomplexes, thereby combining hydrogen-bonding interactions of enantiomeric PLLAs and PDLAs with the association of UPy end groups between macromolecules. Moreover, by the alteration of comonomers repeating units in copolymers, we tuned the rigidity of the macromolecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Microparticles and nanoparticles of stereocomplexes composed of polylactide (PLA) and its copolymers with other aliphatic polyesters receive much attention, because of their potential use in biomedical and pharmaceutical applications. The synthetic route, most widely used for the preparation of biodegradable and biocompatible copolyesters, is based on the sequential ring-opening polymerization (ROP). However, this method of synthesis requires appropriate conditions for the elimination of even traces of impurities, and suppression of segmental exchange by transesterification .…”
Section: Introductionmentioning
confidence: 99%
“…However, when PLLA and PDLA having molecular weights higher than 100 kDa are mixed, homo‐chiral (hc) crystals of respective polymers are likely formed in preference to the stereocomplex (sc) crystals. In our previous study, we demonstrated that stereoblock‐type polylactides (sb‐PLA) combining both PLLA and PDLA sequences in one macromolecular chain exhibited a highly improved stereo complexibility even when they have high molecular weights 6–11 . By the neighboring arrangement of the enantiomeric block sequences, the sc formation can be much easier in the sb‐PLA.…”
Section: Introductionmentioning
confidence: 99%